Green Synthesis and Characterization of Copper-Zinc Alloy Nanoparticles Using Stem Extract of Tinospora cordifolia and Comparative Study of Anti-Microbial Properties - Subedee, Anup; Shrestha, Sita; Ghimire, Sabita; Pathak, Ishwor; Oli, Hari Bhakta; Sharma, Arun Kumar; Pandey, Bishma Raj; Homagai, Puspa Lal; Shrestha, Ram Lal; Bhattarai, Deval Prasad (Amrit Journal, 2023)
Bimetallic nanoparticles are prepared from the combination of two different metals in a certain ratio and are getting importance over monometallic nanoparticles due to their better properties. In this work, copper-zinc nanoparticles (Cu-Zn NPs) have been prepared by reducing the metal precursors using Tinospora cordifolia (Gurjo) stem extract as a reducing, capping, and stabilizing agent. The physicochemical properties of bimetallic nanoparticles have been studied in terms of UV-vis spectra, XRD and FTIR. Biological activities of as-synthesized nanoparticles were tested against Bacillus subtilis, Escherichia coli, and Candida albicans. The Cu-Zn NPs exhibited remarkable antibacterial as well as antifungal activities compared to either nanoparticle alone. Based on the findings, it can be revealed that Cu-Zn NPs can serve as good antimicrobial agent.